(3efgGL GdYGHOjf Edi GdLfIs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s ((3eMeO jYbhH Hf eXaQ Hf oeRgO GdeNUhej s)
(3ChdgG (B:s
(3GdYbHI GdKGdKI hgj YbHI GdYhGFb Ke Ydjc jG WGdH GdYHGOI habc Gddg HOaY GdYhGFb MJi JSJbje YHGOc s
(3BNQgG (B:s
(3EPG oQOJ CYeGdfG EdjfG Efg LhGO cQje agPG eG CQOfG Cf fPcQg aj cjajI TQM Sdhc WQjb GdBNQI hbO hajG GdebUhO Je cJGH efgGL GdYGHOjf Edi GdLfI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs